2014
DOI: 10.1097/acm.0000000000000311
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life and Palliative Care Curricula in Internal Medicine Clerkships

Abstract: Although many IM clerkship directors have implemented formal curricula in EOL/PC, a substantial gap remains between those who have implemented and those who believe it belongs in the clerkship. Time, faculty, cost, and competing demands are the main barriers to implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Eighty-four percent of those surveyed favored integrating EOL instruction into existing courses or clerkships rather than offering a separate course. In a 2014 survey of internal medicine clerkship directors, Shaheen et al 33 found that 76% of those responding believed EOL and palliative care training should occur in the internal medicine clerkship, yet only 44% reported having formal curricula in EOL/palliative care. Smith and Schaefer also promoted the idea of incorporating palliative care training into core clinical clerkships.…”
Section: The United Statesmentioning
confidence: 99%
“…Eighty-four percent of those surveyed favored integrating EOL instruction into existing courses or clerkships rather than offering a separate course. In a 2014 survey of internal medicine clerkship directors, Shaheen et al 33 found that 76% of those responding believed EOL and palliative care training should occur in the internal medicine clerkship, yet only 44% reported having formal curricula in EOL/palliative care. Smith and Schaefer also promoted the idea of incorporating palliative care training into core clinical clerkships.…”
Section: The United Statesmentioning
confidence: 99%
“…A survey of clerkship directors revealed that lectures and small-group discussions were the most common palliative training modalities. 49 However, residents and directors of pediatric residency programs have reported palliative care learning was best accomplished at the bedside (close to an actual encounter) and during rounds as experiential learning opportunities. 45 Structured home visits and hospice rotations within palliative care curricula would enhance personal and professional trainee development.…”
Section: Training Interventions: Instructional Strategiesmentioning
confidence: 99%
“…Beyond advance directives, the presence of a completed POLST form assures a greater likelihood that an individual's preferences for medical treatment will be honored at the end of life. 1,2 For more than 10 years, the National POLST Paradigm Task Force has assisted states in developing quality standards for POLST programs. To date, 19 states have endorsed POLST programs, 25 have developing programs and 3 states have programs that do not conform to requirements.…”
Section: Descriptionmentioning
confidence: 99%
“…Current approaches to PC teaching are inadequate, primarily preclinical, poorly integrated, focused on knowledge rather than skills and attitudes, and lack opportunity for reflection (Billings, 1997). A survey of Clerkship Directors found 75.8% of respondents felt that PC curricula should occur in clerkships, but only 43.6% had formal curricula (Shaheen, 2014). Early clinical experiences with critical illness, death, and dying have implications on development of students' professional identity, attitudes, and behaviors (Ratanawongsa, 2005 (Fields, 2011).…”
Section: Impact Of An Inpatientmentioning
confidence: 99%
See 1 more Smart Citation